2004
DOI: 10.1086/380800
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Epstein‐Barr Virus during Infectious Mononucleosis

Abstract: Infectious mononucleosis is the clinical manifestation of primary infection with Epstein-Barr virus (EBV). We monitored primary infection during convalescence and during the establishment of persistent infection. The profiles of EBV strains in the oral cavity and in peripheral blood were determined by use of a heteroduplex tracking assay specific for the EBV gene encoding latent membrane protein 1. Multiple EBV strains were detected in most patients and persisted in and were possibly transmitted among 3 distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 32 publications
3
38
0
1
Order By: Relevance
“…The results of this study are also consonant with the observed transition of multiple EBV strains from blood to oral epithelium (44) and the continuously evolving populations of multiple EBV strains seen in the oral secretions of healthy persons (34,42) and mononucleosis patients (7,35) and in oral Control cells and oral surgical biopsy tissue sections from HIV-positive subjects were examined by in situ hybridization for latency-associated EBER transcription and replication-associated BHLF1 transcription. Tissues were imaged by fluorescence laser scanning confocal microscopy.…”
Section: Cd11csupporting
confidence: 80%
“…The results of this study are also consonant with the observed transition of multiple EBV strains from blood to oral epithelium (44) and the continuously evolving populations of multiple EBV strains seen in the oral secretions of healthy persons (34,42) and mononucleosis patients (7,35) and in oral Control cells and oral surgical biopsy tissue sections from HIV-positive subjects were examined by in situ hybridization for latency-associated EBER transcription and replication-associated BHLF1 transcription. Tissues were imaged by fluorescence laser scanning confocal microscopy.…”
Section: Cd11csupporting
confidence: 80%
“…4) (85). In previous studies, compartmental differences in strain prevalence were detected between the oral cavity and PBL in asymptomatic carriers and infectious mononucleosis patients (83,84).…”
Section: Analysis Of the Transmembrane Domain Sequence Of Lmp1mentioning
confidence: 87%
“…After centrifugation through a cesium chloride step gradient, the DNA was dialyzed, proteinase K digested, phenol-chloroform extracted, and ethanol precipitated. The throat wash sample was purified as previously described (83).…”
Section: Methodsmentioning
confidence: 99%
“…However, these assays are more qualitative than quantitative. More-recent studies have employed PCR-based analyses (heteroduplex tracking assays or cloning and Sanger sequencing) to demonstrate particular heterogeneities of LMP1 sequences (13,14).…”
Section: Importancementioning
confidence: 99%